(untitled) (The Review of Diabetic Studies, 2025)
Background Healthcare-associated infections (HAIs) pose a major global challenge, with 136 million annual cases of antibiotic-resistant HAIs, particularly in middle-income countries, leading to millions of deaths, extended hospital stays, and costs up to 45 billion in the US. High-touch surfaces facilitate pathogen transmission via fomites and biofilms of multidrug-resistant organisms like MRSA and C. difficile, exposing limitations of conventional cleaning methods.​ Methods This narrative review synthesizes peer-reviewed literature on emerging antimicrobial coatings and self-disinfecting materials, covering historical development (pre-2000 metals to post-2016 bio-mimetics), mechanisms (anti-adhesive, contact-active, release-based, hybrid), material categories (inorganic nanoparticles, polymers, nanomaterials), fabrication techniques (PVD, sol-gel, electrospinning), clinical applications, challenges, and future directions.​ Results Advanced coatings achieve >99% bacterial reductions on implants, stents, and high-touch surfaces, with hybrids like Ag-Cu nanoparticles and stimuli-responsive systems outperforming single mechanisms against biofilms. Clinical trials show sustained efficacy in orthopedics, ICUs, and PPE, though biocompatibility, durability, and regulatory hurdles persist.​ Conclusions Self-disinfecting materials offer promising HAI prevention through multifunctional, AI-optimized designs, warranting scaled implementation in resource-limited settings to combat antimicrobial resistance.​